ENSURING UNINTERRUPTED POWER SUPPLY TO RESIDENTIAL AND SMALL INDUSTRIAL CONSUMERS DURING BLACKOUTS - STASIV, ANDRII; SYSAK, IVAN (Herald of Khmelnytskyi National University. Technical sciences, 2025)
In this paper the authors consider the urgent problem of ensuring uninterrupted power supply to household and small industrial consumers in blackout conditions caused by technogenic, natural and military factors. Specific examples of large-scale power outages in various countries around the world, including countries in Europe (Spain, Portugal) and Asia (Indonesia) are given, and the situation in Ukraine is analyzed, as the problem of ensuring energy supply here has become particularly acute due to regular attacks of critical infrastructure. Comparative analysis of the well-known technical solutions for backup power supply including gasoline and diesel generators, systems based on solar panels with batteries, uninterruptible power supplies (UPS), integrated hybrid systems, and modern mobile charging stations is carried out. The advantages and disadvantages of each of the options, taking into account current realities and consumer needs are identified. Particular attention is paid to practicality, environmental friendliness, financial feasibility, ease of use, autonomy and mobility. Detailed investigation of the efficiency of the application of portable charging stations, which combine rechargeable power sources with the possibility of fast charging both from the mains and from solar panels, is proposed as a promising area. The key parameters for choosing such devices, including capacity, rated and peak power, connector types, charging time, and mobility level are analyzed in this paper. Recommendations for the selection of charging station depending on the type of load, which makes it possible to organise rationally the autonomous power supply for household or small business under conditions of unstable power supply are given. The obtained results are valuable for the practical implementation of solutions in order to ensure autonomous energy supply, especially in regions experiencing systematic outages, and can be used for further scientific and technical investigations in the field of energy security.